Education and happiness in the school-to-work transition - Dockery, Alfred Michael (National Centre for Vocational Education Research, 2010)
Education is generally seen as enhancing people's lives. However, previous research has reported an inverse relationship between education and happiness or satisfaction with life: as education level goes up, happiness goes down. Using data from the Longitudinal Surveys of Australian Youth (LSAY), this report examines the relationship between education and happiness. The impact of factors such as family circumstances and personality traits are also considered. The report finds that undertaking vocational qualifications such as an apprenticeship has a positive impact on happiness both during the training period and after completion. For university graduates, however, happiness declines following completion of their study.